Performance Assessment of Amorphous HfO2-Based RRAM Devices for Neuromorphic Applications. (5th August 2021) - Ossorio, O. G.; Vinuesa, G.; García, H.; Sahelices, B.; Dueñas, S.; Castán, H.; Pérez, E.; Mahadevaiah, M. K.; Wenger, Ch.
Abstract : The use of thin layers of amorphous hafnium oxide has been shown to be suitable for the manufacture of Resistive Random-Access memories (RRAM). These memories are of great interest because of their simple structure and non-volatile character. They are particularly appealing as they are good candidates for substituting flash memories. In this work, the performance of the MIM structure that takes part of a 4 kbit memory array based on 1-transistor-1-resistance (1T1R) cells was studied in terms of control of intermediate states and cycle durability. DC and small signal experiments were carried out in order to fully characterize the devices, which presented excellent multilevel capabilities and resistive-switching behavior.